2020
DOI: 10.1007/s10120-020-01110-3
|View full text |Cite
|
Sign up to set email alerts
|

Reappraise role of No. 10 lymphadenectomy for proximal gastric cancer in the era of minimal invasive surgery during total gastrectomy: a pooled analysis of 4 prospective trial

Abstract: Background For patients with locally advanced proximal gastric cancer (LAPGC), the individualized selection of patients with highly suspected splenic hilar (No. 10) lymph node (LN) metastasis to undergo splenic hilar lymphadenectomy, is a clinical dilemma. This study aimed to re-evaluate the feasibility and safety of laparoscopic spleen-preserving splenic hilar lymphadenectomy (LSPSHL) and to identify the population who would benefit from it. Methods A total of 1068 patients (D2 group = 409; D2 + No. 10 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…Oh et al ( 26 ) showed that splenectomy patients had a poorer short-surgical outcome than spleen-preservation patients, and the survival analysis indicated that the 5-year OS of the spleen-preservation group was significantly higher than that of the splenectomy group in pN0 advanced GC patients. Zhong et al ( 27 ) study indicated that laparoscopic spleen-preserving No. 10 node dissection for GC was safe and feasible, and the 3-year OS of D2+ No.…”
Section: Splenic Hilar (No 10) Ln Dissection With or Without Splenectomy For Proximal Gcmentioning
confidence: 99%
“…Oh et al ( 26 ) showed that splenectomy patients had a poorer short-surgical outcome than spleen-preservation patients, and the survival analysis indicated that the 5-year OS of the spleen-preservation group was significantly higher than that of the splenectomy group in pN0 advanced GC patients. Zhong et al ( 27 ) study indicated that laparoscopic spleen-preserving No. 10 node dissection for GC was safe and feasible, and the 3-year OS of D2+ No.…”
Section: Splenic Hilar (No 10) Ln Dissection With or Without Splenectomy For Proximal Gcmentioning
confidence: 99%
“…In this subgroup, the 3-year overall survival rate of the D2+ no. 10 group increased compared to the D2 group [ 77 ]. Consequently, the Japanese guideline mentions station 10 dissection as a low-evidence option for proximal carcinoma infiltrating the greater curvature [ 4 ].…”
Section: Standard Resection Proceduresmentioning
confidence: 99%
“…One study referred to the posterior No. 10 LND (22); and six studies did not reveal sufficient outcome information to perform analysis (23)(24)(25)(26)(27)(28). Finally, eight retrospective cohort studies involving 4,131 patients were included in the study (14,(29)(30)(31)(32)(33)(34)(35).…”
Section: Selection Of Trialsmentioning
confidence: 99%